Neoliberalism and insecurity in advanced capitalism - Long, Michael A.; Fullerton, Andrew S.; Stretesky, Paul B. (Routledge, 2025)
"This book examines the relationship between neoliberalism and insecurity beginning with the post-World War II period and continuing up through the present. Neoliberalism - the dominant political economic perspective which elevates competition above all else at both the structural and individual levels - has increased the amount of insecurity (e.g., food, energy, job) across the world. It provides a theoretical and empirical analysis of how and why neoliberalism and insecurity have become intertwined over the last half century. The book takes a novel approach to the study of neoliberalism, insecurity, and their intersection. First, in addition to examining specific types of insecurity, the overall concept of insecurity is defined and theorized as a fundamental part of neoliberal capitalism. Second, to help bypass the structural vs. individual binary that has come to characterize much of the neoliberalism literature, a field-theoretic framework heavily influenced by the work of Pierre Bourdieu, is employed. As such, it will be of great interest for researchers in neoliberalism, insecurity, and Bourdieu's theory of practice - including advanced undergraduate students and graduate scholars from sociology, anthropology, geography, political science, and public health"-- Provided by publisher.
Keywords: Neoliberalism -- History.; Food supply -- History.; Power resources -- History.; Competition -- History.; Capitalism -- History.; elektronické knihy; electronic books